Low-dose Actinomycin-D treatment re-establishes the tumoursuppressive function of P53 in RELA -positive ependymoma - Tzaridis, Theophilos-Dimitrios; Milde, Till; Pajtler, Kristian Wilfried; Kulozik, Andreas; Witt, Olaf; Korshunov, Andrey; Pfister, Stefan; Witt, Hendrik (OncoTarget, 2016)
Oncotarget | https://doi.org/10.18632/oncotarget.11452 Theophilos Tzaridis, Till Milde, Kristian W. Pajtler, Sebastian Bender, David T. W. Jones, Simone Müller, Andrea Wittmann, Magdalena Schlotter, Andreas E....
Gesehen am 15.12.2017